Representations of Muslims in the coverage of the Charlie Hebdo attack in selected U.S. news media / Dayana Nayan - Dayana, Nayan (2017)
Studies looking at the representations of Islam and Muslims in Western media indicate that Islam and Muslims tend to be portrayed in a predominantly negatively manner. This explains why the media has the power to disseminate its ideologies to its readers. It cannot be denied that the media is filled with powerful ideological-loaded texts contributing to the way misconceptions of Islam and Muslims in the real world are being created. This study, which examines news articles from two selected U.S news media namely, the Fox News and Huffington Post, aims to investigate how Muslims are represented during the coverages of the Charlie Hebdo attack. The representations of Muslims are studied by looking at how they are being named and referred to and what kind of qualities and attributes are being predicated about them in news discourse. This attempt to analyse the representations of the Muslims as social actors is realised through the application of Van Leeuwen’s socio-semantic network model. The analysis of this study reveals that there is evidence to suggest that the Muslim social actors are negatively portrayed but there is also some evidence of positive representations followed by some level of dichotomous representations in both news media. Four dominant themes emerged in the negative constructions of the Muslim social actors namely, the association of Muslims with terrorism and extremism, the depiction of Muslims as violent, the depiction of Muslims as opposing Western values and the depiction of Muslims as criminals. The alternative discourses present the Muslim social actors as victims, peaceful, and integrating well with the French society. The ideological implications of such representations towards Muslims (hence Islam) are are discussed in the study. As such, there is evidence that both news media echo the Orientalist formation of a discourse despite the alternative discourse provided.